Relationship Between Drug Consumption, Supervisors' Knowledge and Support, and Patients' Obedience to Take Tuberculosis Drugs - Ni Luh Widani; Sondang Ratnauli Sianturi (IJNP (Indonesian Journal of Nursing Practices), 2020)
Background: Tuberculosis (TB) is a disease caused by Mycobacterium Tuberculosis generally attacking lungs, and the treatment is a minimum of six months. The recovery of TB clients requires adherence to medication treatment and Drug Consumption Supervisors (PMO). Objective: This study aims to analyze the relationship between drug consumption, supervisors' knowledge and support, and patients' obedience to take tuberculosis drugs.Method: This research employed a quasi-experiment with a total population sampling technique. The study was conducted in May-August 2019 in sector one, East Jambe, Karawang district (4 villages), and it employed 101 respondents of TB patients and 101 respondents of supervisors (family). Analysis in this study is used in the Spearman Rho Test.Result: The supervisor analysis reveals that 71.3% of the supervisors are 25-49 years old, 59.4% of them are female, 80.1% of them are unemployed, 70.3% of them have low education, and 52.5% of them are married couples. TB patient analysis reveals that 59.4% of the patients are 25-49 years old, 63.4% of them are male, and 59.4% of them have new TB The level of supervisors' knowledge is good at 78.2%, and their support is good at 63.4%, while the patients' adherence to taking drugs is good at 93.1%. The relationship analysis reveals there is no relationship between the supervisors' knowledge and patient's medication adherence (p-value 0.13); otherwise, there is a significant relationship between the supervisors' support and drug-taking adherence (p-value 0.04).Conclusion: The supervisors' knowledge does not affect adherence, but their support significantly influences the patients' obedience of taking TB drugs.